2006
DOI: 10.5863/1551-6776-11.2.92
|View full text |Cite
|
Sign up to set email alerts
|

An Open Label Comparison of Calfactant and Poractant Alfa Administration Traits and Impact on Neonatal Intensive Care Unit Resources

Abstract: OBJECTIVE To compare calfactant (CA) and poractant alfa (PA) administration traits, short-term clinical responses, and resource use in the neonatal respiratory distress syndrome (RDS) setting. METHODS An open label series of 277 (213 PA and 64 CA) infants was evaluated for 445 administrations. Registered respiratory therapists collected patient, surfactant administration, and postadministration clinical data. Economic analysis involved labor costs of surfactant administration and usage, wastage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The similarity of the pattern of usage between calfactant and poractant alfa observed in this report replicates 1 of the 2 previous reports comparing the usage be-tween these 2 surfactants. In addition to Jeon et al, 11 Gerdes et al 12 reported calfactant patients averaging 1.72 doses and poractant alfa patients averaging 1.67 doses. 12 The Gerdes et al 12 experience is almost identical to the average per patient dosing of 1.6 for calfactant patients and 1.7 for poractant alfa patients observed in this experience.…”
Section: Discussionmentioning
confidence: 90%
“…The similarity of the pattern of usage between calfactant and poractant alfa observed in this report replicates 1 of the 2 previous reports comparing the usage be-tween these 2 surfactants. In addition to Jeon et al, 11 Gerdes et al 12 reported calfactant patients averaging 1.72 doses and poractant alfa patients averaging 1.67 doses. 12 The Gerdes et al 12 experience is almost identical to the average per patient dosing of 1.6 for calfactant patients and 1.7 for poractant alfa patients observed in this experience.…”
Section: Discussionmentioning
confidence: 90%
“…11 Very low birth weight infants were enrolled in a sequential, non-randomized, open label fashion at a major teaching hospital. In the 31-month study period, poractant alfa was used for the first 23 months, and calfactant was used for the latter 8 months.…”
Section: Natural Product Comparisonsmentioning
confidence: 99%
“…Gerdes et al [31] in an open-label comparison of calfactant with poractant 4 alfa showed cost benefits favoring poractant alfa. In a cost-minimization analysis comparing poractant alfa and beractant, Marsh et al [32] reported significant cost savings with poractant alfa treatment compared to beractant.…”
Section: Natural Modified Surfactantsmentioning
confidence: 99%
“…Ten studies have compared the three natural surfactants, eight [24][25][26][27][28][29] were randomized controlled trials and two were retrospective studies [30,31] . Four of the eight trials compared beractant with calfactant and the other four trials compared beractant with poractant alfa.…”
Section: Natural Modified Surfactantsmentioning
confidence: 99%